Use of a sequential chimeric perforator flap for one‐stage reconstruction of complex soft tissue defects of the extremities. Issue 2 (22nd March 2019) - Qing, Liming; Wu, Panfeng; Yu, Fang; Zhou, Zhengbing; Tang, Juyu
Abstract : Background: One‐stage reconstruction of complex soft tissue defects of the extremities is a challenging problem. Repair of complex soft tissue defects requires adequate skin tissues to cover the large surface wound and special tissues for obliterating the dead space. The chimeric flap is one of the most popular approaches for reconstruction of complex soft tissue defects. However, the problems of donor‐site morbidity and inability to repair very large defects at one‐stage remain. The purpose of this study was to present our clinical experience using sequential chimeric perforator flaps for reconstruction of complex extremity defects with primary closure of the donor site. Methods: From August 2013 to March 2017, 12 patients with complex soft tissue defects underwent extremity reconstruction using sequential chimeric perforator flaps, which were composed of a chimeric anterolateral thigh perforator (ALTP) flap and an additional free perforator flap. The skin paddles were placed side‐by‐side to cover the large surface soft tissue defects, and the muscle component was used to obliterate the dead space. Of these patients, one was injured by a crushing accident, while the other 11 patients were injured in traffic accidents. Results: The size of the skin paddles ranged from 26 cm × 8 cm–10 cm × 6 cm to 30 cm × 8.5 cm–29 cm × 9 cm. The muscle paddle size ranged from 2 cm × 3 cm × 4 cm to 22 cm × 4 cm × 2 cm. All‐components of the sequential chimeric flaps survived in all‐patients. Vascular compromise was observed in one case. One case suffered minor wound‐edge necrosis and was treated conservatively. Primary closure of donor‐site was successfully achieved in all‐patients, and all‐donor‐site wounds healed uneventfully. The mean follow‐up time was 15.25 months. Most of the cases showed a satisfactory contour, and only two patients presented with mildly bulky appearance that treated with a debulking procedure. Conclusions: The sequential chimeric perforator flap is an alternative procedure for reconstruct complex soft tissue defects of the extremities. This approach allows for flexible design, a larger cutaneous area, and low donor site morbidity.